2000
DOI: 10.1002/1097-4644(20001201)79:3<486::aid-jcb130>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

LINE L1 retrotransposable element is targeted during the initial stages of apoptotic DNA fragmentation

Abstract: Using a directional cloning strategy, DNA sequence information was obtained corresponding to the site of early radiation-induced apoptotic DNA fragmentation within the human lymphoblastoid cell line TK6. Data were obtained from 88 distinct clones comprising approximately 65 kbp of sequenced material. Analysis of all cloned material showed that sequences in the 10 bp immediately adjacent to the cleavage sites were enriched in short oligoT tracts. The proportion of repetitive DNA within the entire cloned materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…Therefore, our results point to a random cleavage of the chromatin during apoptosis. This is different from other reports that found preferential sites of apoptotic DNA cleavage, 26,27,28 but there is an equal number of reports supporting our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, our results point to a random cleavage of the chromatin during apoptosis. This is different from other reports that found preferential sites of apoptotic DNA cleavage, 26,27,28 but there is an equal number of reports supporting our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…6,38 However, others have shown that the activation of endogenous and several exogenous nucleases also results in DNA digestion in the proximity of MARs and produces similar sets of high molecular weight 50 and 300 kb fragments as those generated by topoisomerase II inhibitors. 7,36 More direct evidence that MARs are specific targets for early DNA cleavage came recently from the study of Khodarev et al 39 These authors performed a directional cloning of DNA ends corresponding to high molecular weight chromatin fragments produced during radiation-induced apoptosis, and found them to contain ATrich MAR-like sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the application of pulsed-field gel electrophoresis showed that prior to or in the absence of internucleosomal cleavage, chromosomal DNA is cleaved into large fragments of 50-300 kb. 12,13 The sequence of the cleavage sites is A/Trich, as found in the nuclear scaffold region, 14 suggesting that chromatins are cleaved by a nuclease at the nuclear scaffold attachment sites. A different requirement for metal ions (Mg which efficiently undergo apoptotic DNA fragmentation.…”
Section: Identification Of the Dnase Responsible For The Apoptotic Dnmentioning
confidence: 96%